Elimination of lymphatic filariasis in the Gambia. - Maria P Rebollo; Sana Malang Sambou; Brent Thomas; Nana-Kwadwo Biritwum; Momodou C Jaye; Louise Kelly-Hope; Alba Gonzalez Escalada; David H Molyneux; Moses J Bockarie (Public Library of Science (PLoS), 2015)
BACKGROUND:The prevalence of Wuchereria bancrofti, which causes lymphatic filariasis (LF) in The Gambia was among the highest in Africa in the 1950s. However, surveys conducted in 1975 and 1976 revealed a dramatic decline in LF endemicity in the absence of mass drug administration (MDA). The decline in prevalence was partly attributed to a significant reduction in mosquito density through the widespread use of insecticidal nets. Based on findings elsewhere that vector control alone can interrupt LF, we asked the question in 2013 whether the rapid scale up in the use of insecticidal nets in The Gambia had interrupted LF transmission. METHODOLOGY/PRINCIPAL FINDING:We present here the results of three independently designed filariasis surveys conducted over a period of 17 years (1997-2013), and involving over 6000 subjects in 21 districts across all administrative divisions in The Gambia. An immunochromatographic (ICT) test was used to detect W. bancrofti antigen during all three surveys. In 2001, tests performed on stored samples collected between 1997 and 2000, in three divisions, failed to show positive individuals from two divisions that were previously highly endemic for LF, suggesting a decline towards extinction in some areas. Results of the second survey conducted in 2003 showed that LF was no longer endemic in 16 of 21 districts surveyed. The 2013 survey used a WHO recommended LF transmission verification tool involving 3180 6-7 year-olds attending 60 schools across the country. We demonstrated that transmission of W. bancrofti has been interrupted in all 21 districts. CONCLUSIONS:We conclude that LF transmission may have been interrupted in The Gambia through the extensive use of insecticidal nets for malaria control for decades. The growing evidence for the impact of malaria vector control activities on parasite transmission has been endorsed by WHO through a position statement in 2011 on integrated vector management to control malaria and LF.